(untitled) (Historias, 2004)
This article analyses the behavior of General Lázaro Cárdenas’s government towards so called “undesirable foreigners”, particularly towards Spaniards in a nation with a long tradition of hispanophobia. Article 33 of the Mexican Constitution has been the tool used by the government to expel foreigners considered as undesirable. This paper studies the use of this legislation during Cárdenas’s presidency. It underlines the differences from previous administrations, and shows the surveillance and control systems used against Spanish residents in Mexico who supported Francisco Franco during the Spanish Civil War.